Odd hours auspicious caesarean sections - Kaur, Harpreet; Shukla, Veena; Mathur, Sharda; Mathur, Arun (International Journal Of Community Medicine And Public Health, 2019)
In clinical practice, various obstetrical indications lead to the need to perform caesarean section deliveries in order to ensure maternal safety and favourable neonatal out comes. World Health Organization (WHO), in accordance with scientific evidence has stated that maximum safe limit of caesarean sections in any region throughout the globe is 10-15%. However, many countries including India have shown much higher rates during researches. Socio cultural factors like auspicious dates and time of deliveries also have a hidden role to play in these rising caesarean trends, in which the babies are delivered at the desired day and time for bright future as predicted by astrologers. This practice may be full of hazards and complications for mother, baby, as well as the medical and paramedical personnel. In addition, the resource crunch created in society by unnecessary surgeries may also hamper treatment of deserving patients.